Competition in Microfinance Institutions: Does Voluntary Saving Product Have a Moderating Role? - Nisa, Chaerani; Viverita, Viverita; Chalid, Dony Abdul (Jurnal Keuangan dan Perbankan, 2023)
This study investigates the effect of competition and the moderating role of voluntary savings on the outreach and sustainability of Microfinance Institutions (MFIs). The study uses data from 39 countries and 609 MFIs from 2004 to 2018. Unit of analysis in this study includes all MFIs in the Mix Market database. It uses Boone Indicator to measure competition. In addition, this study uses the random effects model to regress the model. We find that competition corresponds with decreased outreach and sustainability, but the value is insignificant.  The first research question is how competition affects MFIs’ outreach and sustainability, and the second research question is whether voluntary savings can work as a moderating variable in the relationship between competition and MFIs’ outreach and sustainability. Findings of this study provide guidance to MFIs and regulators regarding the ideal form for MFIs whether they should prioritize lending or expand their services to include voluntary savings. DOI: 10.26905/jkdp.v27i4.11014